THE APPLICATION OF PEER FEEDBACK STRATEGY TO IMPROVE STUDENTS’ WRITING ACHIEVEMENT IN NARRATIVE TEXT - Muhammad Ibrahim Siregar; Sri Minda Murni (LINGUISTICA, 2013)
ABSTRACT This study concerned on the application of peer feedback strategy to improve students’ achievement in writing narrative text. The objective of this study was to investigate to what extent the application of Peer Feedback strategy in teaching improved students’ narrative writing achievement. This research applied classroom action research. Subjects of this research were the first year students of SMA Negeri 18 Medan class X-1consisted of 34 students. This research was conducted in two cycles. Each cycle was organized in four steps, namely Planning, Action, Observation, and Reflection where Cycle II was the improvement of Cycle I. Quantitative data (writing test) and qualitative data (observation sheet, questionnaire sheet, field note) were collected. Findings showed that students’ mean score improved from Post-Test in Cycle I to Post-Test in Cycle II. Students’ mean score in Post-Test in Cycle I was 68.08, and in Post-Test in Cycle II was 74.70. The data gathered from observation sheet and field note showed that students’ expression and enthusiastic also improved. Thus, it was found that the application of peer feedback strategy in teaching significantly improved students’ achievement in writing narrative text. It is suggested that English teachers apply this strategy in teaching narrative text writing. Keywords: Peer Feedback Strategy, Writing, Narrative Text.